Health-risk behaviours and injuries among youth and young adults in chiang mai, thailand: A population-based survey - Apichai Wattanapisit (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. This study aimed to identify the prevalence of health-risk behaviours (alcohol use, tobacco smoking and gambling) and the associations between health-risk behaviours and injuries among youth (15–24 years) and young adults (25–39 years). A multi-stage cluster sampling survey was conducted in Chiang Mai, Thailand. The associations between health-risk behaviours and injuries were analysed using logistic regression and adjusted for potential confounders. Sample weights were applied in all analyses. Six-hundred-and-thirty participants were included. Fifty-three percent of males and 12.3% of females drank in the past three months. Smoking in the past three months was higher among males (38.5%) than females (0.7%). About a quarter of men and a fifth of the women had gambled in the past year. A total of 6.4% of males and 4.8% of females sought medical attention in the past year due to injuries. Compared to those without any of the three health-risk behaviours, the odds ratio for injuries requiring medical attention was 3.81 (95% CI: 1.33 to 10.90, p = 0.013) for those with two health-risk behaviours and 13.8 (95% CI: 4.24 to 45.10, p < 0.001) for those with all three health-risk behaviours. Injury prevention policies may need to incorporate interventions designed to assess multiple health-risk behaviours.